PENINGKATAN KEMAMPUAN MENULIS KATA DALAM TEKS NARASI EKSPOSITORIS MELALUI MODEL PEMBELAJARAN BERSIKLUS (CYCLE LEARNING) PADA SISWA KELAS VIII C SMP NEGERI 3 MANOKWARI - Lasol, Apriani Irma Beatrix (Universitas Papua Manokwari, 2017)
This study aims to illustrate the ability to use the proper wording according to general guidelines EYD by students of class VIII C SMP Negeri 3 Manokwari. Learning model used in this research is cycle learning model, which is student centered learning model. Cycle learning. Characteristic of learning cycle learning model is each student individually learns learning materials that have been prepared by teachers. Then, individual learning outcomes are taken to groups to be discussed by group members and all group members are jointly responsible for the overall answers. But in this study, students will learn individually. Because students will be assigned to write expository narrative text based on personal experience by using proper wording according to EYD. As for the formulation of the problem in research are: (1) How the ability of writing the word according to EYD in expository narrative text on students of class VIII C SMP Negeri 3 Manokwari ?, and (2) Whether the learning model cycle (cycle learning) can improve the ability of writing according to EYD in expository narrative text in grade VIII C students of SMP Negeri 3 Manokwari ?. Subjects in the study were students of class VIII C SMP Negeri 3 Manokwari with a total of 43 students consisting of 23 female students and 20 male students.